Bone induction material and preparation method thereof

By designing glass carbon materials with a three-period extremely small curved lattice structure and performing surface modification treatment, the problem of deformation and unstable mechanical properties of glass carbon materials during the preparation process is solved, and the preparation of large-size and excellent mechanical properties of osteoinducible materials is achieved, and the osteoinducible ability in bone repair is achieved.

CN119587747AInactive Publication Date: 2025-03-11SICHUAN HUADING CENTURY TECHNOLOGY CO LTD

Patent Information

Application Number
CN202411878272.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2024-10-22
Filing Date
2024-12-19
Publication Date
2025-03-11
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

In the prior art, glass carbon materials have problems such as deformation, foaming, crushing, and cracking during the preparation process, resulting in unstable mechanical properties and difficulty in preparing complex shapes and large-sized glass carbon materials, which limits their application in the fields of osteoinduction and osteogenesis implantation.

Method used

By designing glass carbon materials with a three-period extremely small curved surface lattice structure, and using 3D printing technology to prepare polymer polymer scaffolds, followed by surface modification treatment, including solvent method, molten salt etching, CO2 etching and other methods, bone-induced materials with coral-like or coral-like morphology are formed.

Benefits of technology

The preparation of glass carbon materials with large size, controllable pyrolysis deformation, uniform structure and few microscopic defects is achieved. It has excellent mechanical properties and osteoinduction capabilities, and can accelerate the repair and regeneration of bone tissue during bone repair.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119587747A_ABST
    Figure CN119587747A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of material preparation, and particularly relates to a bone induction material and a preparation method thereof. The invention firstly provides the bone induction material, wherein the bone induction material is prepared from a glassy carbon material subjected to surface modification; the glassy carbon material subjected to surface modification has a coral-like or coral-like morphology, and the coral-like or coral-like morphology comprises a straight line, an arc line, a branched structure, a circular ring or circular ring-like structure and / or a bead-like morphology formed by self-assembly of nanoparticles; the coral-like or coral-like morphology also comprises a non-uniform hole structure. The invention innovatively provides that the carbon material can have a bone induction effect, and proves that the bone induction material prepared by taking the glassy carbon material as the matrix has the capability of accelerating bone tissue repair and regeneration.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] Priority application This application claims priority to the Chinese invention patent application [CN2024114799352] "A superstructure glassy carbon and its preparation method and application" filed on October 22, 2024, which is incorporated by reference in its entirety. Technical Field

[0002] The present invention belongs to the technical field of material preparation, and in particular relates to an osteoinductive material and a preparation method thereof. Background Art

[0003] Bone defect treatment has a great clinical need, and bone tissue regeneration and repair is very important, but the lack of advanced bone regeneration and repair materials is a current problem. Compared with autologous bone and allogeneic bone, artificial bone repair materials provide an important means for bone defect treatment due to their wide sources and no immune rejection. They are critical for improving the ability to promote bone tissue regeneration and repair.

[0004] Titanium is often used in the manufacture of implants, but titanium itself is not an osteogenic component and does not have osteoinductive activity. Currently, calcium phosphate coatings (such as hydroxyapatite) are plasma sprayed onto the titanium surface to simulate the inorganic components of bone tissue. However, titanium has a high elastic modulus and stress shielding, which can affect bone healing. Titanium also has radiographic ray shielding artifacts, which can affect clinicians' diagnosis.

[0005] In addition, there are strategies to prepare osteoinductive materials by combining hydroxyapatite with other polymer materials or other biomaterials. For example, the patent with publication number CN105013002A and invention name “Absorbable Bioactive Osteoinductive Material and Preparation Method Thereof” discloses an osteoinductive material prepared by compounding low-crystallinity calcium phosphate powder and collagen or gelatin solution, but this material has the problem of low mechanical strength and incompatibility with human bones.

[0006] Based on this, it is necessary to propose new methods and strategies to improve the shortcomings of existing technologies.

[0007] Glassy carbon is a type of amorphous carbon that usually has good mechanical properties, electrical conductivity, biocompatibility and chemical stability, and has important application value in the fields of biomedicine, energy, aerospace, etc. At present, the preparation method of glassy carbon is usually to pyrolyze polymer precursors at high temperature under vacuum or inert gas. The pyrolysis process will cause a large volume shrinkage, which can easily lead to deformation, foaming, breakage, cracking and other problems, which seriously limits the development and application of glassy carbon materials. In addition, under the current technological level, glassy carbon materials still have the contradiction of low mechanical properties of complex shapes and difficulty in customizing structures with good mechanical properties, and this contradiction becomes more obvious as the size of the glassy carbon material increases. Therefore, there are no reports in the prior art on the use of glassy carbon materials in the fields of osteogenic implants, bone induction, etc. Summary of the invention

[0008] In view of this, the object of the present invention is to provide an osteoinductive material and a preparation method to alleviate or partially alleviate the deficiencies existing in the prior art in the field. The present invention specifically adopts the following technical solutions.

[0009] A bone induction material is prepared from a surface-modified glassy carbon material; the glassy carbon material has a stable structure with uniformly distributed stress in all directions; the superstructure glassy carbon uses a unit cell of a three-period minimal surface as the minimum repeating unit; the unit cell of the three-period minimal surface includes a diamond or diamond-like structure; the surface-modified glassy carbon material has a coral-like or coral-like morphology, the coral-like or coral-like morphology includes a straight line, an arc, a branched structure, a ring or a ring-like structure and / or a beaded morphology formed by self-assembly of nanoparticles; the coral-like or coral-like morphology also includes an inhomogeneous pore structure.

[0010] Furthermore, the means for changing the surface morphology include solvent treatment, molten salt etching, CO 2 Etching or plasma treatment.

[0011] Furthermore, the means for changing the surface morphology also includes introducing functional groups, proteins, peptides and / or small molecule drugs onto the surface.

[0012] In some preferred embodiments, the functional groups include carbonyl, hydroxyl, carboxyl, epoxy, vinyl, alkoxy, thiol, amino, azide and / or alkyne, but are not limited thereto.

[0013] Furthermore, the three-periodic minimal surface includes a digital model that satisfies the following characteristics: (1)Sin(x)sin(y)sin(z)+sin(x)cos(y)cos(z)+cos(x)sin(y)cos(z)+cos(x)cos(y)sin(z) = 0, (2)cos(x)sin(y)+cos(y)sin(z)+sin(x)cos(z)=0, (3)sin(x)sin(y)sin(z)+sin(2x)sin(y)+sin(2y)sin(z)+sin(2z)sin(x)-cos(x)cos(y)cos(z)+sin(2x)cos(z)+cos(x)sin(2y)+cos(y)sin(2z)=0 Or (4)2(cos(x)cos(y)+cos(y)cos(z)+cos(z)cos(x)) –(cos(2x)+cos(2y)+cos(2z))=0.3.

[0014] Furthermore, the glassy carbon material is obtained by pyrolyzing a high molecular polymer support with the same structure and then carbonizing it in equal proportion.

[0015] The “same structural unit” means that the polymer scaffold also has a stable structure with uniform stress distribution in all directions; it also uses the unit cell of the three-period minimal surface as the minimum repeating unit; the unit cell of the three-period minimal surface includes a diamond or diamond-like structure.

[0016] In some preferred embodiments, the high molecular polymer comprises a high carbon content polymer; the high carbon content polymer comprises furan resin, furfuryl alcohol resin, furfuryl ketone resin, phenolic resin, epoxy resin, polyurethane, polyimide, polyethylene glycol, acrylic resin, polylactic acid, polycaprolactone, polyethylene, polyetheretherketone, nylon, polycarbonate, polymethyl methacrylate, polyvinyl butyral, polyethylene terephthalate, polyacrylonitrile, polyvinylidene fluoride, polyvinylidene chloride, polystyrene, polybutadiene, polyphenylene oxide, polyphenylene sulfide, polybutene-1, polybenzimidazole, polyaryletherketone, polyarylsulfone, polynaphthalene diol One or more materials selected from the group consisting of polyethylene formate, polyaniline, polyacetylene, polyparaphenylene, polyphthalimide, polyphenylene vinylene, polylactide, polychloroprene, cyanoacrylate, polynaphthylene vinylene, polyparaxylene, polymethylphenylsiloxane, liquid crystal polymer, polythiophene, polyvinyl acetylene, polyoxadiazole, polybisphenol A, polyacrylonitrile-butadiene-styrene copolymer, polychlorotrifluoroethylene, polyepoxy resin-acrylate copolymer, polybenzoquinone, polyparaphenylene sulfone, polyphenylene, polybenzoxazole, polypiperidine, polyvinyl acetal, polybenzothiazole and polyvinyl pyrrolidone, but are not limited thereto.

[0017] In some preferred embodiments, the surface average curvature of the three-periodic minimal surface structure ranges from -0.135 to 0.137.

[0018] As a preferred implementation, the surface average curvature of the three-periodic minimal surface structure is 0.

[0019] A method for preparing an osteoinductive material comprises the following steps: S01: Design and construct a three-dimensional digital model with a three-periodic minimal surface lattice structure, the three-dimensional digital model includes (1)Sin(x)sin(y)sin(z)+sin(x)cos(y)cos(z)+cos(x)sin(y)cos(z)+cos(x)cos(y)sin(z) = 0, (2)cos(x)sin(y)+cos(y)sin(z)+sin(x)cos(z)=0, (3)sin(x)sin(y)sin(z)+sin(2x)sin(y)+sin(2y)sin(z)+sin(2z)sin(x)-cos(x)cos(y)cos(z)+sin(2x)cos(z)+cos(x)sin(2y)+cos(y)sin(2z)=0 Or (4)2(cos(x)cos(y)+cos(y)cos(z)+cos(z)cos(x)) –(cos(2x)+cos(2y)+cos(2z))=0.3; S02: using the three-dimensional digital model designed and constructed in S01 as a template for 3D printing, wherein the material used for the 3D printing includes a polymer to obtain a polymer scaffold; S03: performing surface modification treatment on the polymer stent, wherein the surface modification treatment means includes solvent treatment; the surface of the polymer stent after surface modification has a coral-like or coral-like morphology, wherein the coral-like or coral-like morphology includes straight lines, arcs, branched structures, rings or ring-like structures and / or beaded morphologies formed by self-assembly of nanoparticles; the coral-like or coral-like morphology also includes a non-uniform pore structure; S04: pyrolyzing the surface-modified high molecular polymer scaffold obtained in S03, and proportionally reducing and carbonizing the surface-modified high molecular polymer scaffold after pyrolysis to obtain the osteoinductive material.

[0020] The present invention also provides another alternative method for preparing the osteoinductive material.

[0021] A method for preparing an osteoinductive material comprises the following steps: S01: Design and construct a three-dimensional digital model with a three-periodic minimal surface lattice structure, the three-dimensional digital model includes (1)Sin(x)sin(y)sin(z)+sin(x)cos(y)cos(z)+cos(x)sin(y)cos(z)+cos(x)cos(y)sin(z) = 0, (2)cos(x)sin(y)+cos(y)sin(z)+sin(x)cos(z)=0, (3)sin(x)sin(y)sin(z)+sin(2x)sin(y)+sin(2y)sin(z)+sin(2z)sin(x)-cos(x)cos(y)cos(z)+sin(2x)cos(z)+cos(x)sin(2y)+cos(y)sin(2z)=0 Or (4)2(cos(x)cos(y)+cos(y)cos(z)+cos(z)cos(x)) –(cos(2x)+cos(2y)+cos(2z))=0.3; S02: using the three-dimensional digital model designed and constructed in S01 as a template for 3D printing, wherein the material used for the 3D printing includes a polymer to obtain a polymer scaffold; S03: pyrolyzing the high molecular polymer scaffold obtained in S02, and carbonizing the pyrolyzed high molecular polymer scaffold in equal proportion to obtain a glassy carbon material; S04: performing surface modification treatment on the glassy carbon material to obtain the osteoinductive material, wherein the surface modification treatment method includes molten salt etching, CO 2 Etching or plasma treatment; the glassy carbon material after surface modification has a coral-like or coral-like morphology, wherein the coral-like or coral-like morphology includes straight lines, arcs, branched structures, rings or ring-like structures and / or beaded morphologies formed by self-assembly of nanoparticles; the coral-like or coral-like morphology also includes a non-uniform pore structure.

[0022] In some preferred embodiments, the molten salt etching method includes treating at high temperature with one or more of sodium chloride, potassium chloride, magnesium chloride, sodium fluoride, calcium fluoride, lithium chloride and / or calcium chloride, but is not limited thereto.

[0023] In some preferred embodiments, the solvent treatment includes placing the polymer scaffold in a solution at room temperature for self-assembly. When a scaffold made of an amphiphilic polymer material is soaked in water, the amphiphilicity of the polymer material will cause self-assembly on the surface of the polymer scaffold to form a micelle-like structure deposited on the surface of the polymer scaffold, and then sintered to finally form the coral-like or coral-like morphology.

[0024] Furthermore, the 3D printing used includes liquid crystal display printing technology, digital light processing printing technology, two-photon printing technology, extrusion printing technology or powder laser sintering printing technology.

[0025] Furthermore, the pyrolysis is performed by heating at normal pressure in an inert gas, wherein the inert gas comprises one or more gases selected from the group consisting of nitrogen, argon, helium and neon.

[0026] Furthermore, the sintering equipment used in the pyrolysis process operation includes equipment selected from muffle furnace, tubular furnace or hot isostatic pressing sintering furnace.

[0027] In some preferred embodiments, the high molecular polymer comprises a high carbon content polymer; the high carbon content polymer comprises furan resin, furfuryl alcohol resin, furfuryl ketone resin, phenolic resin, epoxy resin, polyurethane, polyimide, polyethylene glycol, acrylic resin, polylactic acid, polycaprolactone, polyethylene, polyetheretherketone, nylon, polycarbonate, polymethyl methacrylate, polyvinyl butyral, polyethylene terephthalate, polyacrylonitrile, polyvinylidene fluoride, polyvinylidene chloride, polystyrene, polybutadiene, polyphenylene oxide, polyphenylene sulfide, polybutene-1, polybenzimidazole, polyaryletherketone, polyarylsulfone, polynaphthalene diol One or more materials selected from the group consisting of polyethylene formate, polyaniline, polyacetylene, polyparaphenylene, polyphthalimide, polyphenylene vinylene, polylactide, polychloroprene, cyanoacrylate, polynaphthylene vinylene, polyparaxylene, polymethylphenylsiloxane, liquid crystal polymer, polythiophene, polyvinyl acetylene, polyoxadiazole, polybisphenol A, polyacrylonitrile-butadiene-styrene copolymer, polychlorotrifluoroethylene, polyepoxy resin-acrylate copolymer, polybenzoquinone, polyparaphenylene sulfone, polyphenylene, polybenzoxazole, polypiperidine, polyvinyl acetal, polybenzothiazole and polyvinyl pyrrolidone, but are not limited thereto.

[0028] Furthermore, the means for changing the surface morphology also includes introducing functional groups, protein polypeptides and / or small molecule drugs onto the surface.

[0029] The osteoinductive material is obtained by the above preparation method.

[0030] Application of the above-mentioned osteoinductive materials in bone repair.

[0031] Application of the above-mentioned osteoinductive material in the preparation of bone repair devices.

[0032] On the other hand, the present application can also provide another alternative technical solution.

[0033] A bone inductive material, the bone inductive material is prepared from a surface-modified glassy carbon material; the surface-modified glassy carbon material has a coral-like or coral-like morphology, the coral-like or coral-like morphology comprises straight lines, arcs, branched structures, rings or ring-like structures and / or beaded morphologies formed by self-assembly of nanoparticles; the coral-like or coral-like morphology also comprises a non-uniform pore structure.

[0034] Furthermore, the means for changing the surface morphology include solvent treatment, molten salt etching, CO 2 Etching or plasma treatment.

[0035] Furthermore, the means for changing the surface morphology also includes introducing functional groups, proteins, peptides and / or small molecule drugs onto the surface.

[0036] In some preferred embodiments, the functional groups include carbonyl, hydroxyl, carboxyl, epoxy, vinyl, alkoxy, thiol, amino, azide and / or alkyne, but are not limited thereto.

[0037] Furthermore, the glassy carbon material is obtained by carbonizing a high molecular polymer support having the same structure after pyrolysis.

[0038] In some preferred embodiments, the high molecular polymer comprises a high carbon content polymer; the high carbon content polymer comprises furan resin, furfuryl alcohol resin, furfuryl ketone resin, phenolic resin, epoxy resin, polyurethane, polyimide, polyethylene glycol, acrylic resin, polylactic acid, polycaprolactone, polyethylene, polyetheretherketone, nylon, polycarbonate, polymethyl methacrylate, polyvinyl butyral, polyethylene terephthalate, polyacrylonitrile, polyvinylidene fluoride, polyvinylidene chloride, polystyrene, polybutadiene, polyphenylene oxide, polyphenylene sulfide, polybutene-1, polybenzimidazole, polyaryletherketone, polyarylsulfone, polynaphthalene diol One or more materials selected from the group consisting of polyethylene formate, polyaniline, polyacetylene, polyparaphenylene, polyphthalimide, polyphenylene vinylene, polylactide, polychloroprene, cyanoacrylate, polynaphthylene vinylene, polyparaxylene, polymethylphenylsiloxane, liquid crystal polymer, polythiophene, polyvinyl acetylene, polyoxadiazole, polybisphenol A, polyacrylonitrile-butadiene-styrene copolymer, polychlorotrifluoroethylene, polyepoxy resin-acrylate copolymer, polybenzoquinone, polyparaphenylene sulfone, polyphenylene, polybenzoxazole, polypiperidine, polyvinyl acetal, polybenzothiazole and polyvinyl pyrrolidone, but are not limited thereto.

[0039] Beneficial technical effects: The present invention solves the contradiction between the shape, size and mechanical properties of glassy carbon materials to a certain extent. By designing a structure with uniform stress, a superstructure glassy carbon with both mechanical and shape design can be prepared. In addition, the present invention also innovatively proposes that carbon materials can have an osteoinductive effect, and proves that the osteoinductive material prepared with glassy carbon materials as the matrix has the ability to accelerate the repair and regeneration of bone tissue, which is specifically described as follows.

[0040] (1) The present invention uses a three-periodic minimal surface lattice superstructure design and utilizes the excellent pyrolysis shrinkage stress uniform distribution behavior of the lattice structure to prepare glassy carbon with large size, controllable pyrolysis deformation, uniform structure, and few microscopic defects. The glassy carbon is further surface-modified or the polymer scaffold of the glassy carbon before pyrolysis is surface-modified to successfully prepare an osteoinductive material. The surface of the osteoinductive material has a unique coral-like or coral-like morphology, which can induce bone tissue to accelerate repair and regeneration. In addition, this osteoinductive material also takes into account excellent mechanical properties, can provide good support during bone repair, and can be customized into a unique shape according to actual needs, so it has broad application prospects in the field of medical devices.

[0041] (2) The present invention adopts the existing 3D printing technology, and does not make too many changes to the preparation and pyrolysis process of the existing glassy carbon bracket. It only performs a unique three-periodic minimal surface lattice design on the original glassy carbon material. Its production process is simple and easy to achieve mass production. BRIEF DESCRIPTION OF THE DRAWINGS

[0042] In order to more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings required for use in the embodiments or the prior art descriptions are briefly introduced below. In all the drawings, similar elements or parts are generally identified by similar reference numerals. In the drawings, each element or part is not necessarily drawn according to the actual scale. Obviously, the drawings described below are some embodiments of the present invention. For those of ordinary skill in the art, other drawings can also be obtained based on these drawings without paying creative labor.

[0043] Figure 1 A model diagram of a three-periodic minimal surface lattice structure (support structure) provided for one of the embodiments of the present invention; Figure 2 A graphic example of a coral-like or coral-like shape in one embodiment of the present invention; FIG3 is a scanning electron microscope image of a glassy carbon scaffold having a surface nanostructure obtained by solvent surface treatment in one embodiment of the present invention (A is soaked in water, B is soaked in ethanol, and the scale bars are both 20 μm); Figure 4This is a scanning electron microscope image of a glassy carbon stent with a surface micro-nano morphology structure obtained after molten salt treatment in one embodiment of the present invention (scale bar is 1 μm); Figure 5 One embodiment of the present invention is through CO 2 The electron microscope image of the rough micro-nano morphology obtained by gas etching (scale bar is 40μm); Figure 6 This is a result verification of the change in surface hydrophilicity after plasma treatment of one of the embodiments of the present invention (1 in the figure represents after the modification, and 0 represents before the modification); Figure 7 This is a diagram showing the calcium-phosphorus deposition effects of ordinary glassy carbon and surface-treated glassy carbon; Figure 8 The hydrophilicity test of the glassy carbon material after plasma treatment in one embodiment of the present invention; Fig. 9 Schematic diagram of surface-modified glassy carbon materials used for bone repair and their efficacy (the left side of a is superstructured glassy carbon, the right side is a blank control, and b and c are the effects of superstructured glassy carbon used for bone repair at different visual angles); Fig.10 This is the bone induction result after the surface-modified glassy carbon material was implanted into the muscle (the green mark in the figure represents the increase of CT value, and the purple represents bone tissue cells); Fig.11 To verify that glassy carbon materials composited with hydroxyapatite have more significant ability to promote bone regeneration; Fig.12 To verify that glassy carbon with surface micro-nano structure has more significant and efficient bone regeneration ability than titanium alloy; Fig.13 This is a physical picture of centimeter-scale superstructure glassy carbon prepared in one of the embodiments of the present invention; Fig.14 This is a verification diagram of the thermal shrinkage performance of common structural glassy carbon prepared in one of the comparative examples of the present invention; Fig.15 To verify that superstructure carbons of different sizes have the ability to shrink in equal proportions (A is the shrinkage of glassy carbons of different sizes in equal proportions after high-temperature pyrolysis under the same conditions, and B is the shrinkage rate of glassy carbons of different sizes in different directions); Fig.16 Scanning electron microscope images of microscopic defects of different glassy carbon materials (A is the superstructure glassy carbon of the present invention, B is the common structure glassy carbon, scale bar is 200μm); Fig.17 This is the maximum compressive strength result diagram of different glassy carbon materials; Fig.18 To verify that the superstructure glassy carbon of the present invention has excellent mechanical properties; Fig.19 The stress distribution diagram of the finite element analysis of the three-periodic minimal surface lattice structure proposed by the present invention; Fig. 20 A schematic diagram of the structure of the three-periodic minimal surface lattice structure proposed by the present invention in three directions of XYZ; Fig.21 This is another example of the present invention showing the calcium-phosphorus deposition results on the surface of glassy carbon after surface modification (A is calcium deposition, B is phosphorus deposition). DETAILED DESCRIPTION

[0044] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0045] Herein "and / or" includes any and all combinations of one or more of the associated listed items.

[0046] Herein, "plurality" means two or more than two, ie, it includes two, three, four, five, etc.

[0047] As used in this specification, the term "about" typically means + / - 5% of the stated value, more typically + / - 4% of the stated value, more typically + / - 3% of the stated value, more typically + / - 2% of the stated value, even more typically + / - 1% of the stated value, and even more typically + / - 0.5% of the stated value.

[0048] In this specification, some embodiments may be disclosed in a format of being in a range. It should be understood that this description of "being in a range" is only for convenience and brevity, and should not be interpreted as a rigid limitation on the disclosed range. Therefore, the description of the range should be considered to have specifically disclosed all possible sub-ranges and independent numerical values ​​within this range. For example, the description of the range 1-6 should be considered to have specifically disclosed sub-ranges such as from 1 to 3, from 1 to 4, from 1 to 5, from 2 to 4, from 2 to 6, from 3 to 6, etc., as well as individual numbers within this range, such as 1, 2, 3, 4, 5 and 6. Regardless of the breadth of the range, the above rules apply.

[0049] Definition of noun: The “uniform distribution of stress in all directions” mentioned in the present invention means that the static stress analysis results in the X, Y and Z directions of the three-periodic minimal surface lattice structure of the present invention all show uniform static stress distribution.

[0050] The "superstructure" mentioned in the present invention refers to a structure that simultaneously satisfies the three-periodic minimal surface mentioned in the present invention and the stable structure with uniform stress of diamond or diamond-like carbon.

[0051] The "diamond-like structure" described in the present invention refers to a modification of a regular tetrahedral structure similar to diamond, wherein the modification includes a slight change in bond angle or edge length.

[0052] The “proportional reduction” mentioned in the present invention means that during the pyrolysis change of the three-periodic minimal surface structure described in the present invention, the shrinkage rate in each direction is the same or close.

[0053] Example 1 This embodiment provides an example of a surface-modified or surface-modified glassy carbon material.

[0054] First, a glassy carbon material is prepared. It is understood that the glassy carbon material shown in this embodiment is only an example and should not be construed as a limitation. The specific steps are as follows.

[0055] Step 1: Use 3D modeling software to design and construct a three-dimensional digital model with a three-periodic minimal surface lattice structure (support structure). The three-dimensional digital model equations involved (hereinafter referred to as "equations") are as follows.

[0056] (1) Type D: Sin(x)sin(y)sin(z)+sin(x)cos(y)cos(z)+cos(x)sin(y)cos(z)+cos(x)cos(y)sin(z)=0 (2) Type G: cos(x)sin(y)+cos(y)sin(z)+sin(x)cos(z)=0 (3) CY type: sin(x)sin(y)sin(z)+sin(2x)sin(y)+sin(2y)sin(z)+sin(2z)sin(x)-cos(x)cos(y)cos(z)+sin(2x)cos(z)+cos(x)sin(2y)+cos(y)sin(2z)=0 (4) IWP type: 2(cos(x)cos(y)+cos(y)cos(z)+cos(z)cos(x))–(cos(2x)+cos(2y)+cos(2z))=0.3 The D type is preferred in this embodiment. The three-period minimal surface lattice model designed according to the D type equation is as follows Figure 1 shown.

[0057] Step 2: Using a carbon-rich polymer as a printing material, specifically epoxy resin in this embodiment, and printing through digital light processing printing technology (photocuring printing) to obtain a polymer bracket, also known as a superstructure bracket.

[0058] Step 3: Surface modification of the prepared superstructure scaffold.

[0059] Step 4: Using a muffle furnace, a tubular furnace, a hot isostatic pressing sintering furnace and other equipment, the surface-modified superstructure scaffold prepared in step 3 is heated at normal pressure under the protection of an inert gas, argon. Specifically, the temperature is first raised from room temperature to 250°C for 60 minutes, then raised to 350°C for 100 minutes, kept warm for 120 minutes, then raised by 1 degree every 2 minutes to 700-3000°C, and then naturally cooled to prepare a surface-modified or surface-modified glassy carbon material, i.e., the osteoinductive material of the present invention.

[0060] This embodiment may also provide another alternative means.

[0061] First, a superstructure scaffold is prepared by 3D printing technology, and then the superstructure scaffold is pyrolyzed into a glassy carbon material, and then the glassy carbon material is surface modified to obtain the bone induction material.

[0062] The following are examples of surface modification methods. It should be understood that the following specific implementations are only examples and not limitations.

[0063] (1) Surface solvent treatment: The above-mentioned superstructure scaffolds are subjected to surface post-treatment using water solvents, wherein the immersion temperature is room temperature, to obtain osteoinductive materials.

[0064] (2) Molten salt etching of surface micro-nano morphology: The glassy carbon is treated with a molten salt or a mixed molten salt selected from the group consisting of sodium chloride, potassium chloride, magnesium chloride, sodium fluoride, calcium fluoride, lithium chloride, and calcium chloride at a high temperature of more than 800°C to obtain an osteoinductive material with a rough surface and micro-nano morphology.

[0065] (3) Surface CO 2 Treatment: The glassy carbon is continuously introduced with CO at normal pressure. 2 The gas is heated to 800-1200°C and then cooled to room temperature to obtain an osteoinductive material with surface modification.

[0066] (4) Plasma treatment: The glassy carbon is treated with pure O 2 or Ar and O 2 The mixed gas is used as the gas source using a plasma device, the plasma power is controlled in the range of 50-1000 W, the sample is sputtered for 5-60 minutes, and a hydrophilic surface is obtained.

[0067] Optionally, functional groups, proteins, peptides and / or small molecule drugs can be further introduced on the surface. According to conventional technical means in the art, functional groups or other substances can be connected or introduced on the surface-modified material according to specific needs.

[0068] Results Figure 2-Figure 7 .in Figure 2-Figure 5 is an example of the modified surface microscopic morphology. The modified material surface has a coral-like or coral-like morphology, and the coral-like or coral-like morphology includes straight lines, arcs, branched structures, rings or ring-like structures and / or beaded morphologies formed by self-assembly of nanoparticles (see schematic diagram Figure 2 The coral-like or coral-like morphology also includes a non-uniform pore structure ( Figure 3A ). It is understood that the beaded morphology is formed by the self-assembly of nanoparticles, and can be a relatively regular morphology or an irregular beaded morphology without obvious boundaries. In some cases, the beads formed by the self-assembly of nanoparticles are even fused together when observed by the naked eye.

[0069] in Figure 7 The glassy carbon material etched by molten salt has more obvious calcium-phosphorus deposition, and thus has osteoinductive ability.

[0070] The hydrophilicity of the surface-modified glassy carbon material after plasma treatment in (4) was further tested. The surface-modified glassy carbon material and the unmodified glassy carbon material were placed in black ink, and a paper towel was placed on the top of the carbon material. The carbon material treated with plasma can quickly absorb the black ink, so the paper towel on top can also quickly absorb the ink. The results are shown in Table 1. Figure 8 . It is proved that the glassy carbon material after plasma treatment has super strong water absorption capacity.

[0071] Example 2 This embodiment provides a verification of the application of a surface-modified glassy carbon material in bone repair.

[0072] Experimental process: The osteoinductive material prepared by the solvent method in Example 1 was implanted into the critical bone defect (5 mm in diameter) of the skull of 6-week-old SD rats. Then, at 2 months, the skull of the rats was removed and the efficacy of the ultra-structured glassy carbon on bone repair was analyzed by CT.

[0073] Results: See Fig. 9 , Fig. 9 Schematic diagram of surface-modified glassy carbon materials used for bone repair and therapeutic effect ( Fig. 9 a The left side is modified glassy carbon, and the right side is a blank control. In a, bone tissue can be seen growing in the superstructured glassy carbon. In a 2-month period, it was observed that the holes on the left were significantly smaller than those on the right, proving that the surface-modified glassy carbon material prepared by the present invention has the ability to repair bones. Fig. 9 b and 9c were also verified from different angles.

[0074] Fig.10 When the surface-modified glassy carbon material is implanted in the muscle body, the bone tissue on the surface of the glassy carbon scaffold is induced to form, proving that it can play the role of inducing bone formation (osteoinduction). It is speculated that the special coral-like or coral-like morphology of the surface may have a mechanical effect on the cells. The present invention innovatively proposes that carbon materials produce osteoinduction.

[0075] In other preferred embodiments, the osteoinduction is formed by self-assembly of nanoscale materials.

[0076] In other preferred embodiments, the nanoscale material is surface processed to form a rough surface, and after self-assembly, this uniform rough surface plays a role in bone growth and bone induction.

[0077] Example 3 This example provides another application verification of surface-modified glassy carbon material in bone repair.

[0078] Experimental steps: The modified glassy carbon material obtained by solvent treatment was placed in a hydrothermal reactor, and the surface of the glassy carbon material was composited with hydroxyapatite coating under high temperature and high pressure conditions. The glassy carbon material with hydroxyapatite on the surface and the modified glassy carbon material were implanted into the femoral condyle, and at the predetermined time point, the bone defect specimens of each group were taken out for efficacy evaluation.

[0079] Control experiment: The titanium alloy stent was implanted into the femoral condyle in the same way, and at the predetermined time point, the bone defect specimens were taken out for efficacy evaluation.

[0080] Results Fig.11 and Fig.12 . Fig.11 It can be seen that the modified glassy carbon material composited with hydroxyapatite has a more obvious ability to promote bone regeneration; in the same sample, the entire defect area was fully grown at 12 weeks compared to 4 weeks; there was a blank in the middle of the sample at 4 weeks. Fig.12 It can be seen that the modified glassy carbon material with a nano-beaded morphology on the surface has a more obvious and efficient ability to promote bone regeneration compared to titanium alloy (control) (pink represents the grown bone cells / bone tissue, and the pink part in the super-structured glassy carbon is more than that in titanium alloy).

[0081] Example 4 This example provides performance verification of the glassy carbon material (also called superstructured glassy carbon) prepared in Example 1.

[0082] The "superstructure" described in this embodiment refers to a three-periodic minimal surface lattice structure designed and prepared using the D-type, G-type, CY-type or IWP-type three-periodic minimal surface equation provided in Example 1 of the present invention as a model.

[0083] It is understandable that one or more materials of furan resin, furfuryl alcohol resin, furfuryl ketone resin, phenolic resin, epoxy resin, polyurethane, polyimide, polyethylene glycol, acrylic resin and polyacrylonitrile can also be used as 3D printing materials.

[0084] It is understandable that 3D printing technologies such as LCD, TPP, extrusion printing technology, powder laser sintering printing, etc. can be used.

[0085] It is understandable that inert gases such as nitrogen, helium or neon or a combination thereof may also be used as the protective gas.

[0086] In some preferred embodiments, the superstructure glassy carbon prepared in Example 1 has a porous structure with a size exceeding 5 cm, a pore wall thickness of less than 3 mm, and a porosity greater than 50%. Fig.13 .

[0087] The performance verification of the superstructure glassy carbon material prepared in Example 1 is provided.

[0088] (1) Shrinkage determination The shrinkage rate of the superstructure glassy carbon prepared in Example 1 was measured, and the results showed that the superstructure glassy carbon prepared in Example 1 did not show the phenomenon of uneven shrinkage and stress concentration.

[0089] Control experiment: The ordinary structural glassy carbon precursor was first heated from room temperature to 250°C for 60 minutes, then heated to 350°C for 100 minutes, kept warm for 120 minutes, then heated to 700-3000°C for 2 minutes per degree, and then cooled naturally. Then the shrinkage rate was measured, and the results showed obvious shrinkage unevenness and stress concentration, such as Fig.14 shown.

[0090] (2) Proportional shrinkage verification Superstructure glassy carbon of different sizes was prepared by the method of Example 1, and then the uniform shrinkage test of the glassy carbon bracket was carried out. The results are as follows: Fig.15 shown. Fig.15 As can be seen in A, after high-temperature pyrolysis under the same conditions, glassy carbons of different sizes shrink in the same proportion and their shapes do not change. Fig.15B shows the shrinkage of glassy carbon of different sizes in different directions.

[0091] (3) Microstructure observation The ultrastructured glassy carbon prepared in Example 1 and the common structured glassy carbon prepared in the control experiment (1) were analyzed by scanning electron microscopy for apparent microscopic defects, such as Fig.16 Obvious surface cracks were observed on the common structural glassy carbon, but no similar defects were found on the super-structural glassy carbon prepared in Example 1.

[0092] (4) Mechanical properties verification The superstructure glassy carbon prepared in Example 1 and the common structure glassy carbon prepared in the control experiment (1) were subjected to compression test, and the specific steps are as follows.

[0093] 1cm × 1cm × 1cm glassy carbon material samples were prepared and the maximum compressive strength of the samples was tested using a universal mechanical compressor. The displacement rate of the compressor beam was set to 1mm / min until the sample was broken and the maximum load was recorded. The ratio of the maximum load to the force-bearing area was the maximum compressive strength.

[0094] The experimental results are as follows Fig.17 The maximum compressive strength of the superstructure glassy carbon material sample prepared in Example 1 is 186 MPa, while the maximum compressive strength of the common structure glassy carbon material sample is only 17.59 MPa.

[0095] It is further verified that the superstructure glassy carbon material prepared in Example 1 has excellent mechanical properties, and only 0.1g can withstand a weight of 100kg. Fig.18 .

[0096] (5) Verification of three-periodic minimal surfaces The above four three-periodic minimal surface equations are all based on the definition of three-periodic minimal surfaces. Their common point is that they all have structural periodic repetition in three dimensions, and the average curvature ranges from -0.135 to 0.137.

[0097] More intuitively, the average curvature of each point on the surface is 0.

[0098] Furthermore, this structure with zero curvature has isotropic and uniform stress distribution.

[0099] Therefore, the glassy carbon prepared based on the three-dimensional digital models of the four three-periodic minimal surface equations provided in Example 1 all have the characteristics of large size and super structure.

[0100] Finite element simulation of the three-periodic minimal surface structure of the D-type equation was performed using ABAQUS software. Fig.19. During the simulation, HyperMesh was used for pre-processing and ABAQUS was used for solving. Pre-processing includes geometric processing and removal of some very small features that do not affect the calculation results. Then a mesh size of 0.4 mm was used to generate the mesh, using second-order tetrahedral elements. The total number of elements is 400,814 and the number of nodes is 617,725. The material is set as an elastic-plastic material with a density of 1.1 g / cm³, a Young's modulus of 11 GPa, and a Poisson's ratio of 0.4. One end of the structure is completely fixed, and a 5% compressive strain is applied in three different lattice directions (X, Y, and Z). The stress distribution under compressive strain in different directions was calculated. The results show that when strain is applied in each direction, the model has a uniform stress distribution as a whole, and there is no stress concentration phenomenon. The lower right figure shows that this three-periodic minimal surface lattice structure is proportionally reduced after pyrolysis to form a superstructure glassy carbon.

[0101] The schematic diagram of the structure of the three-periodic minimal surface lattice obtained by the preferred D-type equation design in the X, Y, and Z directions is shown in FIG. Fig. 20 .

[0102] Example 5 This embodiment provides several other examples of preparation methods of superstructure glassy carbon materials, which are as follows.

[0103] Example 1 Step 1: Use 3D modeling software to design and construct a three-dimensional digital model with a three-periodic minimal surface lattice structure. The three-dimensional digital model equations involved (hereinafter referred to as "equations") are as follows.

[0104] (1) Type D: Sin(x)sin(y)sin(z)+sin(x)cos(y)cos(z)+cos(x)sin(y)cos(z)+cos(x)cos(y)sin(z)=0 (2) Type G: cos(x)sin(y)+cos(y)sin(z)+sin(x)cos(z)=0 (3) CY type: sin(x)sin(y)sin(z)+sin(2x)sin(y)+sin(2y)sin(z)+sin(2z)sin(x)-cos(x)cos(y)cos(z)+sin(2x)cos(z)+cos(x)sin(2y)+cos(y)sin(2z)=0 (4) IWP type: 2(cos(x)cos(y)+cos(y)cos(z)+cos(z)cos(x))–(cos(2x)+cos(2y)+cos(2z))=0.3 In this example, type D is preferred.

[0105] Step 2: Use a carbon-rich polymer as the printing material. In this example, furfuryl alcohol resin is used as the material. The polymer scaffold, also known as the superstructure scaffold, is printed using two-photon printing technology.

[0106] Step 3: Use a muffle furnace, a tubular furnace, a hot isostatic pressing sintering furnace and other equipment to heat the superstructure bracket prepared in step 2 at normal pressure under the protection of inert gas argon. Specifically, first heat from room temperature to 250°C for 70 minutes, then heat to 350°C for 80 minutes, keep warm for 100 minutes, then heat by 1 degree every 3 minutes to 700-3000°C, and then cool naturally to prepare a superstructure glassy carbon material.

[0107] Example 2 Step 1: Use 3D modeling software to design and construct a three-dimensional digital model with a three-periodic minimal surface lattice structure. In this example, type D is preferred.

[0108] Step 2: Use a carbon-rich polymer as the printing material. In this example, acrylic resin is used as the material. The polymer bracket, also known as the superstructure bracket, is printed through extrusion printing technology.

[0109] Step 3: Use a muffle furnace, a tubular furnace, a hot isostatic pressing sintering furnace and other equipment to heat the superstructure bracket prepared in step 2 at normal pressure under the protection of inert gas argon. Specifically, first heat from room temperature to 255°C for 100 minutes, then heat to 360°C for 100 minutes, keep warm for 80 minutes, then heat by 1 degree every 5 minutes to 700-3000°C, and then cool naturally to prepare a superstructure glassy carbon material.

[0110] Example 3 Step 1: Use 3D modeling software to design and construct a three-dimensional digital model with a three-periodic minimal surface lattice structure. In this example, type D is preferred.

[0111] Step 2: Use a carbon-rich polymer as the printing material. This example uses polyurethane as the material and prints a polymer scaffold, also known as a superstructure scaffold, through powder laser sintering printing technology.

[0112] Step 3: Use a muffle furnace, a tubular furnace, a hot isostatic pressing sintering furnace and other equipment to heat the superstructure bracket prepared in step 2 at normal pressure under the protection of inert gas argon. Specifically, first heat from room temperature to 260°C for 90 minutes, then heat to 360°C for 90 minutes, keep warm for 120 minutes, then heat by 1 degree every minute to 700-3000°C, and then cool naturally to prepare a superstructure glassy carbon material.

[0113] It should be noted that the above embodiments are merely examples, and are based on the final sintered superstructure glassy carbon material, rather than limitations.

[0114] Example 6 This embodiment provides another application of glassy carbon material in bone induction.

[0115] After the surface of the ordinary structure glassy carbon is modified by the method shown in Example 1, its surface can also form a coral-like or coral-like micro-nano morphology. Further verification shows that the glassy carbon material of Example 1 has a calcium-phosphorus deposition phenomenon that is close to or similar to that of the glassy carbon material, indicating that the surface modification method provided by the present invention and the coral-like or coral-like morphology formed after modification have bone induction effects. The results are shown in Fig.21 , where yellow represents calcium and blue represents phosphorus.

[0116] It should be noted that, in this article, the terms "include", "comprises" or any other variations thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device. In the absence of further restrictions, an element defined by the sentence "comprises a ..." does not exclude the existence of other identical elements in the process, method, article or device including the element.

[0117] The embodiments of the present invention are described above in conjunction with the accompanying drawings, but the present invention is not limited to the above-mentioned specific implementation modes, which are merely illustrative rather than restrictive. Under the guidance of the present invention, ordinary technicians in this field can also make many forms without departing from the scope of protection of the present invention and the claims, all of which are within the protection of the present invention.

Claims

1. An osteoinductive material, characterized in that: The bone induction material is prepared from a surface-modified glassy carbon material; the glassy carbon material has a stable structure with uniformly distributed stress in all directions; the superstructure glassy carbon uses a unit cell of a three-period minimal surface as the minimum repeating unit; the unit cell of the three-period minimal surface includes a diamond or diamond-like structure; the surface-modified glassy carbon material has a coral-like or coral-like morphology, and the coral-like or coral-like morphology includes straight lines, arcs, branched structures, rings or ring-like structures and / or beaded morphologies formed by self-assembly of nanoparticles; the coral-like or coral-like morphology also includes an inhomogeneous pore structure.

2. The osteoinductive material according to claim 1, characterized in that The means for changing the surface morphology include solvent treatment, molten salt etching, CO2 etching or plasma treatment.

3. The osteoinductive material according to claim 1, characterized in that The means for changing the surface properties also includes introducing functional groups, proteins, peptides and / or small molecule drugs on the surface; preferably, the functional groups include carbonyl, hydroxyl, carboxyl, epoxy, vinyl, alkoxy, thiol, amino, azide and / or alkyne.

4. The osteoinductive material according to claim 1, characterized in that: The three-periodic minimal surface includes a digital model that satisfies the following characteristics: (1)Sin(x)sin(y)sin(z)+sin(x)cos(y)cos(z)+cos(x)sin(y)cos(z)+cos(x)cos(y)sin(z) = 0, (2)cos(x)sin(y)+cos(y)sin(z)+sin(x)cos(z)=0, (3)sin(x)sin(y)sin(z)+sin(2x)sin(y)+sin(2y)sin(z)+sin(2z)sin(x)-cos(x)cos(y)cos(z)+sin(2x)cos(z)+cos(x)sin(2y)+cos(y)sin(2z)=0 Or (4)2(cos(x)cos(y)+cos(y)cos(z)+cos(z)cos(x)) –(cos(2x)+cos(2y)+cos(2z))=0.

3.

5. The osteoinductive material according to claim 1, characterized in that The glassy carbon material is obtained by pyrolyzing a high molecular polymer support with the same structure and then carbonizing it by shrinking it in equal proportion.

6. The osteoinductive material according to claim 5, characterized in that The high molecular polymer includes a high carbon content polymer; the high carbon content polymer includes furan resin, furfuryl alcohol resin, furfuryl ketone resin, phenolic resin, epoxy resin, polyurethane, polyimide, polyethylene glycol, acrylic resin, polylactic acid, polycaprolactone, polyethylene, polyetheretherketone, nylon, polycarbonate, polymethyl methacrylate, polyvinyl butyral, polyethylene terephthalate, polyacrylonitrile, polyvinylidene fluoride, polyvinylidene chloride, polystyrene, polybutadiene, polyphenylene ether, polyphenylene sulfide, polybutene-1, polybenzimidazole, polyaryletherketone, polyarylsulfone, polynaphthalate One or more materials selected from the group consisting of ethylene glycol ester, polyaniline, polyacetylene, polyparaphenylene, polyphthalimide, polyphenylene vinylene, polylactide, polychloroprene, cyanoacrylate, polynaphthylene vinylene, polyparaxylene, polymethylphenylsiloxane, liquid crystal polymer, polythiophene, polyvinyl acetylene, polyoxadiazole, polybisphenol A, polyacrylonitrile-butadiene-styrene copolymer, polychlorotrifluoroethylene, polyepoxy resin-acrylate copolymer, polybenzoquinone, polyparaphenylene sulfone, polyphenylene, polybenzoxazole, polypiperidine, polyvinyl acetal, polybenzothiazole and polyvinyl pyrrolidone.

7. The osteoinductive material according to claim 1, characterized in that The surface average curvature of the three-periodic minimal surface structure ranges from -0.135 to 0.

137.

8. A method for preparing an osteoinductive material, characterized in that: The following steps are involved: S01: Design and construct a three-dimensional digital model with a three-periodic minimal surface lattice structure, the three-dimensional digital model includes (1)Sin(x)sin(y)sin(z)+sin(x)cos(y)cos(z)+cos(x)sin(y)cos(z)+cos(x)cos(y)sin(z) = 0, (2)cos(x)sin(y)+cos(y)sin(z)+sin(x)cos(z)=0, (3)sin(x)sin(y)sin(z)+sin(2x)sin(y)+sin(2y)sin(z)+sin(2z)sin(x)-cos(x)cos(y)cos(z)+sin(2x)cos(z)+cos(x)sin(2y)+cos(y)sin(2z)=0 Or (4)2(cos(x)cos(y)+cos(y)cos(z)+cos(z)cos(x)) –(cos(2x)+cos(2y)+cos(2z))=0.3; S02: using the three-dimensional digital model designed and constructed in S01 as a template for 3D printing, wherein the material used for the 3D printing includes a polymer to obtain a polymer scaffold; S03: performing surface modification treatment on the polymer stent, wherein the surface modification treatment means includes solvent treatment; the surface of the polymer stent after surface modification has a coral-like or coral-like morphology, wherein the coral-like or coral-like morphology includes straight lines, arcs, branched structures, rings or ring-like structures and / or beaded morphologies formed by self-assembly of nanoparticles; the coral-like or coral-like morphology also includes a non-uniform pore structure; S04: pyrolyzing the surface-modified polymer scaffold obtained in S03, and proportionally reducing and carbonizing the surface-modified polymer scaffold after pyrolysis to obtain the osteoinductive material; Alternatively, the method for preparing the osteoinductive material comprises the following steps: S01: Design and construct a three-dimensional digital model with a three-periodic minimal surface lattice structure, the three-dimensional digital model includes (1)Sin(x)sin(y)sin(z)+sin(x)cos(y)cos(z)+cos(x)sin(y)cos(z)+cos(x)cos(y)sin(z) = 0, (2)cos(x)sin(y)+cos(y)sin(z)+sin(x)cos(z)=0, (3)sin(x)sin(y)sin(z)+sin(2x)sin(y)+sin(2y)sin(z)+sin(2z)sin(x)-cos(x)cos(y)cos(z)+sin(2x)cos(z)+cos(x)sin(2y)+cos(y)sin(2z)=0 Or (4)2(cos(x)cos(y)+cos(y)cos(z)+cos(z)cos(x)) –(cos(2x)+cos(2y)+cos(2z))=0.3; S02: using the three-dimensional digital model designed and constructed in S01 as a template for 3D printing, wherein the material used for the 3D printing includes a polymer to obtain a polymer scaffold; S03: pyrolyzing the high molecular polymer scaffold obtained in S02, and carbonizing the pyrolyzed high molecular polymer scaffold in equal proportion to obtain a glassy carbon material; S04: The glassy carbon material is subjected to surface modification treatment to obtain the osteoinductive material, wherein the surface modification treatment method includes molten salt etching, CO2 etching or plasma treatment; the glassy carbon material after surface modification has a coral-like or coral-like morphology, and the coral-like or coral-like morphology includes straight lines, arcs, branched structures, rings or ring-like structures and / or beaded morphologies formed by self-assembly of nanoparticles; the coral-like or coral-like morphology also includes an uneven pore structure.

9. The preparation method according to claim 8, characterized in that: The 3D printing used includes liquid crystal display printing technology, digital light processing printing technology, two-photon printing technology, extrusion printing technology or powder laser sintering printing technology; alternatively, pyrolysis is heating at normal pressure in an inert gas, wherein the inert gas contains one or more gases selected from the group consisting of nitrogen, argon, helium and neon.

10. The preparation method according to claim 8, characterized in that: Means for changing the surface morphology also include introducing functional groups, proteins, peptides and / or small molecule drugs onto the surface.

11. The osteoinductive material obtained by the preparation method according to claim 8.

12. Use of the osteoinductive material according to claim 1 or claim 11 in bone repair.

Citation Information

Patent Citations

  • Absorbable bioactive bone inducing material and preparation method thereof

    CN105013002A

  • Preparation method of 3D-printed bone defect stuffing

    CN110025406A

  • 3D printed controllable porous hydroxyapatite bioceramic stent and preparation method thereof

    CN110272273A

  • Bone tissue engineering scaffold as well as preparation method and application thereof

    CN116271222A

  • Preparation method of superstructure glassy carbon material, superstructure glassy carbon material and application

    CN116553930A

Cited By

  • Application of superstructure glassy carbon in promoting bone repair and preparation method of bone repair material

    CN121466359A

  • Superstructural glassy carbon, preparation method therefor and use thereof

    WO2026026814A1